Growth control of Platycodon grandiflorus (Jacq.) A. DC. for production as potted flower - Sabino, João Henrique Ferreira (2020)
Platycodon (Platycodon grandiflorus) is an ornamental species that needs growth control to satisfy the quality standards of the potted flower market. The appropriate management of growth regulators and plant density are fundamental factors to obtain harmony with the pot size. This study aimed to analyze the effects of the paclobutrazol application and plant density on the growth parameters of four varieties of platycodon ‘Astra Semi-Double’, namely Blue, Pink, Lavender and White. Five concentrations of paclobutrazol (0; 1.25; 2.5; 3.75 and 5.0 mg pot -1 ) were investigated in an experiment with two plants per pot, while four plant densities (one, two, three and four plants per pot) were evaluated in another experiment. Both experiments were conducted in greenhouse, from October 2019 to March 2020, with randomized block design and four replications. In addition to growth parameters, chlorophyll contents were also measured in the second experiment. Shoot height, number of branches, leaf area and dry mass of the plant parts decreased with higher concentration of paclobutrazol or with larger number of plants per pot. Flower diameter was not influenced by the paclobutrazol application or plant density. Chlorophyll α and total chlorophyll contents increased with greater plant density. There was varietal effect on the growth parameters and chlorophyll contents of platycodon ‘Astra Semi-Double’. Pink is an early-flowering variety, while Lavender is a late-flowering variety. The concentration of 3.75 mg pot -1 was the most efficient in controlling growth and improving the visual quality of the platycodon varieties for production as potted flower. The cultivation of four plants per pot occasioned the production of flowering stems with a better quality. Keywords: Balloon flower. Paclobutrazol. Plant density.